Virulence Factors in Staphylococcus aureus and Quality of Raw Milk from Dairy Cows in a Semiarid Region of Northeastern Brazil - Araújo, Renata de Moraes Peixoto; Peixoto, Rodolfo de Moraes; Peixoto, Luciana Jatobá e Silva; Gouveia, Gisele Veneroni; Costa, Mateus Matiuzzi da (Acta Scientiae Veterinariae, 2017)
Background: Milk quality is considered unsatisfactory in Brazil due to factors of a social, economic, cultural, and climatic nature. Mastitis is the main disease that affects dairy herds. Microorganisms of the genus Staphylococcus are the most frequently isolated pathogens in cases of mastitis in bovines. Staphylococcus aureus requires more attention because they have the ability to develop resistance to antimicrobials used in the treatment of mastitis. Thus, the aim of the present study was to evaluate virulence factors in isolates of S. aureus as well as analyze the hygienic-sanitary quality of raw milk produced on dairy farms in a semiarid region of northeastern Brazil. Material, Methods & Results: Samples were taken from milk containers at 44 properties. Fifty-eight isolates of Staphylococcus spp. were analyzed and genotypically identified as S. aureus. In the phenotypic characterization, 56.8% (33/58) of the isolates demonstrated moderate biofilm production. In the genotypic characterization (icaA, icaD and bap genes), icaA was the most representative among the isolates. No resistance to cephalothin or oxacillin was found, but 62% (36/58) of the isolates exhibited resistance to ampicillin, amoxicillin, and penicillin. In the genotypic evaluation in response to β-lactam antibiotics, 50% (29/58) of the isolates exhibited the blaZ gene. Total bacterial counts were determined based on the standard plate count and flow cytometry, for which a significant positive correlation was found (r = 0.61, P < 0.01). The somatic cell count was also performed using flow cytometry and demonstrated that 6.8% (3/44) of the properties had values above one million cells per mL. The analysis of Staphylococcus spp. revealed that 20% (9/44) of the properties had significant counts for the production of staphylococcal enterotoxins. Regarding total coliforms, 56.8% (25/44) of the milk analyzed had counts above 1.0 x 103 CFUs/mL. There were no cases of the isolation of Pseudomonas spp. Streptococcus spp. was isolated on 6.8% (3/44) of the properties. The results of the sequencing revealed one isolate to be Lactococcus lactis and two to be Enterococcus spp. Discussion: None of the 58 isolates of S. aureus was classified as negative in the phenotypic characterization of biofilmforming capacity, which suggests the presence of genes involved in this process. Studies have shown that the molecular techniques used to identify ica genes encoding biofilm synthesis are very important for the identification of virulent strains. The isolates demonstrated resistance to β-lactam antibiotics of the class of penicillins, which are the most widely employed antimicrobial agents for the treatment of diseases in dairy herds. The presence of the blaZ gene in 50% of the isolates is in agreement with data reported in other studies developed in northeastern Brazil. In 50% (29/58) of the isolates, the presence of the blaZ gene was not observed. Of these, (8/29) were resistant to ampicillin, amoxicillin and penicillin. This is due to the existence of other bacterial mechanisms. Research has shown that some isolates possessed three mechanisms (blaZ, mecA and msrA) of antimicrobial resistance simultaneously. The results of the quality analyses demonstrate that some properties produce milk of low quality, which underscores the need for management strategies directed at reducing the contamination of the product.